Injury history and perceived knee function as risk factors for knee injury in youth team-sports athletes - Hietamo, J.; Rantala, A.; Parkkari, J.; Leppänen, M.; Rossi, M.; Heinonen, A.; Steffen, K.; Kannus, P.; Mattila, V.; Pasanen, K. (Sports Health: A Multidisciplinary Approach, 2022)
Background: The identification of risk factors for sports injuries is essential before injury prevention strategies can be planned.